2014
DOI: 10.1159/000356963
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Phagocytosis and Intracellular Signaling by an Inhibitory Channel Catfish Leukocyte Immune-Type Receptor: Evidence for Immunoregulatory Receptor Functional Plasticity in Teleosts

Abstract: Immunoregulatory receptors are categorized as stimulatory or inhibitory based on their engagement of unique intracellular signaling networks. These proteins also display functional plasticity, which adds versatility to the control of innate immunity. Here we demonstrate that an inhibitory catfish leukocyte immune-type receptor (IpLITR) also displays stimulatory capabilities in a representative myeloid cell model. Previously, the receptor IpLITR 1.1b was shown to inhibit natural killer cell-mediated cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 62 publications
2
31
0
Order By: Relevance
“…Transfection, selection, sorting, and stable expression of N-terminal HA epitope-tagged pDISPLAY (Invitrogen/Life Technologies, Burlington, ON, Canada) IpLITR 2.6b/IpFcRg-L and pDISPLAY IpLITR 1.1b in RBL-2H3 cells were performed according to the previously described protocols [38]. The IpLITR 2.6b/IpFcRg-L encodes the extracellular Ig-like domains of IpLITR 2.6b (GenBank accession ABI23577) fused with the transmembrane and ITAM-encoding CYT of IpFcRg-L (GenBank accession AF543420), and that chimeric-receptor construct was used to examine ITAM-mediated cellular responses transmitted by the teleost-adaptor IpFcRg-L.…”
Section: Iplitr-expressing Rbl-2h3 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transfection, selection, sorting, and stable expression of N-terminal HA epitope-tagged pDISPLAY (Invitrogen/Life Technologies, Burlington, ON, Canada) IpLITR 2.6b/IpFcRg-L and pDISPLAY IpLITR 1.1b in RBL-2H3 cells were performed according to the previously described protocols [38]. The IpLITR 2.6b/IpFcRg-L encodes the extracellular Ig-like domains of IpLITR 2.6b (GenBank accession ABI23577) fused with the transmembrane and ITAM-encoding CYT of IpFcRg-L (GenBank accession AF543420), and that chimeric-receptor construct was used to examine ITAM-mediated cellular responses transmitted by the teleost-adaptor IpFcRg-L.…”
Section: Iplitr-expressing Rbl-2h3 Cellsmentioning
confidence: 99%
“…For example, the putative stimulatory receptor IpLITR 2.6b can associate with the ITAMcontaining adaptor IpFcRg-L, and when fused as a receptor chimera, the construct IpLITR 2.6b/IpFcRg-L promoted protein tyrosine kinase-mediated signaling and induced ITAMdependent degranulation, cytokine secretion, and phagocytosis in RBL-2H3 cells [36], whereas the ITIM-encoding inhibitoryreceptor IpLITR 1.1b abrogated mouse NK cell-mediated killing responses [37]. However, we recently demonstrated that IpLITR 1.1b also induced phagocytosis when expressed in the RBL-2H3 mast cell line [38]: a commonly used cell model for characterizing receptor-mediated control of innate effector responses [39][40][41][42][43][44][45]. Taken together, the ability to regulate both stimulatory and inhibitory innate immune cell actions reveals the signaling versatility of IpLITR 1.1b and suggests this receptor may use a unique phagocytic mechanism, different from the prototypical ITAM-mediated pathway represented by IpLITR 2.6b/IpFcRg-L.…”
Section: Introductionmentioning
confidence: 97%
“…Also, when the same receptors were expressed in mouse spleen-derived cytotoxic cells, killing of MHC class Ideficient targets was significantly inhibited (36). More recently, it was demonstrated that the inhibitory TS32.17 LITR 1.1b, which in addition to two ITIMs contains an atypical ITAM-like (ExxYx 2 Vx 16 Yx 2 V) sequence and an ITSM in its CYT, also mediated phagocytosis when expressed in rat basophilic leukemia-2H3 cells (39). Although both TS32.17 LITR1.1b and the chimeric activating LITR2.6b/IpFcRg-L receptors were shown to induce ERK1/2 and protein kinase B (Akt)-dependent signal transduction, there were differences in their signaling kinetics and sensitivity to pharmacological inhibitors (64).…”
Section: Discussionmentioning
confidence: 99%
“…Catfish inhibitory LITRs have a neutral transmembrane (TM) and a cytoplasmic tail (CYT) containing one or more ITIMs, whereas activating forms have a charged lysine residue in their TM allowing for association with signaling adaptors and a short CYT. In addition, there are some LITRs with long CYT that contain an atypical ITAM-like sequence, two ITIMs, and a immunoreceptor tyrosinebased switch motif (ITSM) (31,32,(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%
“…As observed in invertebrates, phagocytosis is also part of the conserved innate defense in early vertebrates. However, functional fine-tuning is achieved through specific cellbound receptors, such as the leukocyte immune-type receptor [4] .…”
Section: Foodies Of Innate Immunitymentioning
confidence: 99%